Цифрова трансформація управління персоналом: виклики, можливості та стратегічні орієнтири - Панченко, М. П.; Полозова, О. О. (ХНУРЕ, 2025)
This article examines how digital technologies are transforming human resource management in the era of global digitalization. It focuses on the role of HRM systems, data analytics, AI, and remote work tools in reshaping HR practices and emphasizes the growing importance of digital skills and personalized employee experiences. The paper also outlines key challenges, including resistance to change and data ethics, concluding that digital tools are strategic enablers of organizational transformation in the digital economy.
Keywords: управління персоналом; цифрова трансформація управління